This time It's Personal: City Museums and Contemporary Urban Life - Tisdale, R. (Місто: історія, культура, суспільство, 2017)
The CAMOC conference that took place in Berlin in 2011, with its theme “Participative Strategies in Capturing the Changing Urban World,” is part of a larger discussion that museums in general—and city museums in particular—have been having recently about our collections and whether they are serving our current needs. We have been assessing our collections—what we own versus what we wish we owned—and we are noticing a disconnect. Most of our collections were formed at the turn of the twentieth century, and we’re having a lot of trouble making them fit the stories we want to tell about our cities here in the twenty-first century. So, we’re experimenting with contemporary collecting, and participatory collecting, in an attempt to make our collections more inclusive and more representative. This is important work and we need to do more of it.